Basic human needs as values: Exploring John Dewey’s normative perspective on social philosophy - Mattarollo, Livio (2018)
John Dewey’s project on social philosophy has not been usually considered as an important piece of his thought. However, his writings about such topic constitute a remarkable effort to articulate several novel concepts and ideas which cannot be found elsewhere in his extensive philosophical work. Within this context, the new edition of his “Lectures in Social and Political Philosophy”—a series of lectures Dewey delivered during his stay in China—provides unique material for reviewing his social viewpoint. During this article I aim to explore Dewey’s normative perspective on social philosophy. Taking into account that the pragmatist introduces a “normative picture” and that he identifies a set of basic human needs at its very basis, the main arising question is how to interpret that set of human needs so as to fully understand that normative criterion. As hypotheses, I consider (i) that social philosophy is mainly engaged with practical judgments and (ii) that it is plausible to interpret these basic human needs as values. In order to support these claims, I firstly reconstruct Dewey’s proposal about a third type of social thought. Secondly, I examine his position about values and standards. Thirdly, I analyze his “normative picture” and I consider the “anthropological reading” presented by Roberto Frega (2015). Lastly, I offer a complementary analysis, arguing that it is possible to explain Dewey’s normative standard in a coherent way with respect to the aims of his social thought and, furthermore, that it is possible to avoid any essentialist commitment.